Structural analysis of a cross car beam using finite element models. Issue 6 (7th December 2015) - Pinto, André F. B. P.; Tavares, S.M.O.; César de Sá, José M. A.; de Castro, P.M.S.T.
Abstract : Purpose: – The purpose of this paper is to use PAM-CRASH, a finite element analysis solver, to assess the performance of a mass production vehicle cross car beam (CCB) under an overlap frontal crash scenario (crashworthiness). Simulation results were reviewed according to what is plausible to register regarding some critical points displacements and, moreover, to identify its stress concentrations zones. Furthermore, it was also computed the CCB modal analysis (noise, vibration and harshness (NVH) assessment) in order to examine if its natural modes are within with the original equipment manufacturer (OEM) design targets. Design/methodology/approach: – The available data at the beginning of the present study consisted of the structure CAD file and performance requirements stated by the OEM for NVH. No technical information was available concerning crashworthiness. Taking into account these limitations, it was decided to adapt the requirements for other mass production cars of the same category, as regards dynamic loading. A dynamic explicit code finite element analysis was performed throughout the CCB structure simulating the 120e−3 s crash event. For the modal analysis, there were some necessary modifications to the explicit finite element model in order to perform the analysis in implicit code. In addition, the car body in white stiffness was assigned at the boundaries. These stiffness values are withdrawn from the points where the CCB is attached to the car body's sheet metal components. Findings: – Although the unavailability of published results for this particular CCB model prevents a comparison of the present results, the trends and order of magnitude of the crash simulation results are within the expectations for this type of product. Concerning modal analysis, the steering column first natural frequency has a percent deviation from the design lower bound value of 5.09 percent when local body stiffness is considered and of 1.94 percent with fixed boundary conditions. The other requirement of the NVH assessment regarding a 5 Hz minimum interval between first vehicle CCB mode and the first mode of the steering column was indeed achieved with both boundary configurations. Originality/value: – This study is a further confirmation of the interest of numerical modeling as a first step before actual experimental testing, saving time and money in an automotive industry that has seen an enormous increase of the demand for new car models in the last decade.